KERJASAMA INDONESIA DENGAN ISLAMIC DELOPMENT BANK (IDB) DALAM PROGRAM MEMBER COUNTRIES PARTNERSHIP STRATEGY (MCPS) 2011-2014 - Susanti, Nurvia; Pahlawan, Indra (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research is describes the cooperation between Indonesia and Islamic Development Bank (IDB) in program known as Member Countries Partnership Strategy (MCPS). In this case, Indonesia is country with the largest economy in Southeast Asia with GDP per capita that has been steadily rising. In fact, the GDP growth as much six percent in 2012 and Muslim population in majority. However, the country is still struggling against poverty, educational problem, health- care and infrastructure development. Therefore, to solve this problem Indonesia should cooperate with another country or international organization, like Islamic Development Bank (IDB).The research was obtained by reviewing the literature either from books, journals, theses, reports, and internet. In this research, the author uses neo-liberalist prespective with international cooperate theory by K.J Holsti and Charles H. Cooley , international organization theory by Clive Archer and A. Le Roy Bennet with level analysis in nation-state.Indonesia’s economic plan is follows a 20-year development plan, spanning from 2005 to 2025. It is segmented into 5-year medium-term plans, called the RPJMN with different development priorities. In this research found that the program MCPS has positively contributed to the second phase of medium term plans. Implementation of the project program MCPS applied in education and health-care sector, poverty alleviation, infrastructure sector, and agricultural sector.Keywords: Islamic Development Bank (IDB), Member Countries Partnership Strategy (MCPS), medium-term plans (RPJMN)